... but also just: reflections on the severe God of the Catechism - A. van de Beek (Acta Theologica)
The seemingly harsh texts about God’s justice and wrath in the Heidelberg Catechism turn out to be the core of the comfort that the catechisms proclaims, if we read the catechism contextually. The same is the case with regard to providence when the catechism claims that also poverty and illness come from God’s fatherly hand.